A critical interpretive synthesis of power and mistreatment of women in maternity care - Marta Schaaf; Maayan Jaffe; Özge Tunçalp; Lynn Freedman (Public Library of Science (PLoS), 2023)
Labouring women may be subjected to physical and verbal abuse that reflects dynamics of power, described as Mistreatment of Women (MoW). This Critical Interpretive Synthesis on power and MoW consolidates current research and advances theory and practice through inter-disciplinary literature exploration. The review was undertaken in 3 phases. Phase 1 consisted of topic scoping; phase 2 entailed exploration of key power-related drivers emerging from the topic scoping; and phase 3 entailed data synthesis and analysis, with a particular focus on interventions. We identified 63 papers for inclusion in Phase 1. These papers utilized a variety of methods and approaches and represented a wide range of geographic regions. The power-related drivers of mistreatment in these articles span multiple levels of the social ecological model, including intrapersonal (e.g. lack of knowledge about one's rights), interpersonal (e.g. patient-provider hierarchy), community (e.g. widespread discrimination against indigenous women), organizational (e.g. pressure to achieve performance goals), and law/policy (e.g. lack of accountability for rights violations). Most papers addressed more than one level of the social-ecological model, though a significant minority were focused just on interpersonal factors. During Phase 1, we identified priority themes relating to under-explored power-related drivers of MoW for exploration in Phase 2, including lack of conscientization and normalization of MoW; perceptions of fitness for motherhood; geopolitical and ethnopolitical projects related to fertility; and pressure to achieve quantifiable performance goals. We ultimately included 104 papers in Phase 2. The wide-ranging findings from Phase 3 (synthesis and analysis) coalesce in several key meta-themes, each with their own evidence-base for action. Consistent with the notion that research on power can point us to "drivers of the drivers," the paper includes some intervention-relevant insights for further exploration, including as relating to broader social norms, health systems design, and the utility of multi-level strategies.